OPTIMALISASI PERAN KADER KESEHATAN DALAM MENGELIMINASI TB PARU DIDESA TELUK NAGA TANGERANG BANTEN - Rosya, Ernalinda; Azteria, Veza; Lestari, Sri; Kartini, Kartini; Rangin, Mayliana Perangin; Anam, Khoirul; Putri, Yohana Dwi; Talahaturuson, Meisya; Setiaji, Willian Rosse (Universitas Mataram, 2024)
The high incidence of Pulmonary TB will certainly have an impact on the community. The impact is medical, social, economic, and cultural. The most severe impact is the increase in mortality. The participation of all parties is urgently needed to eradicate pulmonary TB. The pulmonary TB response program involves all parties, including the community, civil society organizations, and public and private care providers. Community empowerment in the health sector, called health cadres, is crucial in the pulmonary TB elimination program. This community service activity aims to foster partnerships with health cadres. The activities carried out provide knowledge about pulmonary TB to health cadres and train health cadres on how to provide health education to the community. The method used in this activity is interactive health education and training cadres through role play. A pre-test was carried out before the activity, followed by a post-test after the material was delivered. The results of health education activities about pulmonary TB in cadres showed increased knowledge before and after health education was given. Evaluation of training activities with the evaluation results shows that the first cadre scored 78 and the second obtained 79. The shortcomings that need to be addressed are that cadres are not allowed to ask their audiences questions, and there needs to be more positive reinforcement and evaluation of material that has yet to be done. Health education carried out interactively has provided new learning experiences for health cadres. Training on how to provide health education improves the skills of cadres in providing health education to the community.